The impact of anabolic androgenic steroids abuse and type of training on left ventricular remodeling and function in competitive athletes - Ilić, Ivan; Djordjević, Vitomir; Stanković, Ivan; Vlahović-Stipac, Alja; Putniković, Biljana; Babić, Rade; Nešković, Aleksandar N. (Vojnosanitetski pregled, 2014)
Background/Aim. Long-term intensive training is associated with distinctive cardiac adaptations which are known as athlete’s heart. The aim of this study was to determine whether the use of anabolic androgenic steroids (AAS) could affect echocardiographic parameters of left ventricular (LV) morphology and function in elite strength and endurance athletes. Methods. A total of 20 elite strength athletes (10 AAS users and 10 non-users) were compared to 12 steroid-free endurance athletes. All the subjects underwent comprehensive standard echocardiography and tissue Doppler imaging. Results. After being indexed for body surface area, both left atrium (LA) and LV end-diastolic diameter (LVEDD) were significantly higher in the endurance than strength athletes, regardless of AAS use (p < 0.05, for both). A significant correlation was found between LA diameter and LVEDD in the steroid-free endurance athletes, showing that 75% of LA size variability depends on variability of LVEDD (p < 0.001). No significant differences in ejection fraction and cardiac output were observed among the groups, although mildly reduced LV ejection fraction was seen only in the AAS users. The AAS-using strength athletes had higher A-peak velocity when compared to steroid-free athletes, regardless of training type (p < 0.05 for both). Both AAS-using and AAS-free strength athletes had lower e’ peak velocity and higher E/e’ ratio than endurance athletes (p < 0.05, for all). Conclusions. There is no evidence that LV ejection fraction in elite athletes is altered by either type of training or AAS misuse. Long-term endurance training is associated with preferable effects on LV diastolic function compared to strength training, particularly when the latter is combined with AAS abuse.